Politisasi Agama: Ayat-Ayat Politik Dalam Kontestasi Pemilu 2019 Perspektif Tafsir Al-Misbah - I, Idris; Djailani, Syahrul Mubarak (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This research discusses the construction of interpretation on Q.S. Al-Maida: 51, Q.S. Al-Hujurat: 13, and Q.S. An-Nisa: 59 in Tafsir al-Misbah by M. Quraish Shihab, as well as its use by Indonesian political parties in the 2019 elections. The method used was qualitative with a figure thematic approach. The main findings show that the verses were interpreted to strengthen the political positions and ideological campaigns of each party, namely PPP, Golkar, and PDIP. The results of the study show that there is a correlation between religious interpretation and political interest in the dynamics of Indonesian democracy.